Development of tourism villages in Tegal Bungur Village, Natar Subdistrict, South Lampung Regency through a community empowerment approach - Bursan, Rinaldi; Ramelan, Mudji Rachmat (Research and Social Study Institute, 2024)
The development of tourism villages in Tegal Bungur Village, Natar Subdistrict, South Lampung Regency utilizes the potential of nature, culture, and local resources as a tourist attraction that can improve the welfare of the local community. This community empowerment activity aims to increase the literacy of the villages’ community in Natar Subdistrict regarding the development of tourism villages so that they can actively participate in educational development, especially regarding entrepreneurship and tourism education. The methods in this activity consisted of initial survey, training, monitoring, and evaluation. Through the active involvement of the local community in the entire development process, the villages’ community in Natar Subdistrict can optimize their local potentials in a sustainable manner. In this context, solid collaboration among the government, local community, and other relevant parties is important to create a conducive environment for the development of tourism villages. Tegal Bungur Village serves as an example for other villages in optimizing their local potentials for sustainable development of tourism villages. Strong synergy between various parties will provide significant benefits to improve local economic growth, cultural preservation, and community welfare in Tegal Bungur Village and the surrounding regions.